1995
DOI: 10.1016/s0377-1237(17)30989-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycotic Keratitis

Abstract: Mycotic keratitis is a distressing infection and may lead to permanent blindness. Fifty two cases of suspected mycotic keratitis were studied from Jan 91 to Sep 94. Specimens were collected on swabs in 2 0 cases and by corneal scraping in 32 cases. Wet mount examination of the specimens revealed fungal elements in 8 (15.4%) cases, of which 3 specimens were collected on swabs and 5 by corneal scraping. Fungi were isolated from a total of 12 (23.1%) specimens 5 of which were obtained by swabs while 7 by corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…A large study of fungal keratitis in Madras [4], observed only 5 per cent cases out of 698 cases studied to be caused by Curvularia. Other studies from Lucknow [5] and Pune [6] did not show any case of curvularia keratitis. Single case report of curvularia keratitis have also appeared in the literature [7].…”
Section: Discussionmentioning
confidence: 71%
“…A large study of fungal keratitis in Madras [4], observed only 5 per cent cases out of 698 cases studied to be caused by Curvularia. Other studies from Lucknow [5] and Pune [6] did not show any case of curvularia keratitis. Single case report of curvularia keratitis have also appeared in the literature [7].…”
Section: Discussionmentioning
confidence: 71%